The Role of Geomorphology in Phisical Geography and its Application in Research - Sutikno, Sutikno (Forum Geografi, 1990)
Geomorphology as a part of earth sciences has a already knownÂ  for along time, however the development and application is relatively slow, especially in Indonesia. There is a tendency that the concept as well as the application of geomprphology will increase rapidly. The aims of this paper are to discuss the concept of geomorphology. The role of geomorphology in the physical geography studies and its application research activities. Geomorphology deal with land form asÂ  subject of study and stressed on relief, processes, materials (lithology and its structure), and chronology has important role in the physical geography. Geomorphology be able to support of other sciences related to physical environment such as geology, pedology, hydrology, and archaelogy. In the practical application, geomorphology can be used in engineering purposed and regional development planning. In the research activities geomorphology can be used as basic frame work to determine sample areas, and also can be used as frame work to land resources evaluation with land form unit as land mapping unit or evaluation unit.Â